2018
DOI: 10.4103/jcrt.jcrt_844_17
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced antitumor effects of radiotherapy combined local nimustine delivery rendezvousing with oral temozolomide chemotherapy in glioblastoma patients

Abstract: Compared to standard therapy, the antitumor effects of rendezvous therapy were more effective in GBM patients without increasing the toxicities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The method of assessing MGMT promoter methylation in these studies included real-time PCR using the ratio of MGMT to the βactin reference gene (ACTB) greater than 2 in 5 studies, 15 , 17 , 18 , 34 , 35 the methylated MGMT /COL2A1 ratio greater than 0 in one study, 20 nested PCR in one study, 37 pyrosequencing in one study, 19 and not specified in 4 trials. 22 , 23 , 27 , 36 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The method of assessing MGMT promoter methylation in these studies included real-time PCR using the ratio of MGMT to the βactin reference gene (ACTB) greater than 2 in 5 studies, 15 , 17 , 18 , 34 , 35 the methylated MGMT /COL2A1 ratio greater than 0 in one study, 20 nested PCR in one study, 37 pyrosequencing in one study, 19 and not specified in 4 trials. 22 , 23 , 27 , 36 …”
Section: Resultsmentioning
confidence: 99%
“…For this analysis, ACNU and Lomustine were grouped together (alkylating nitrosourea). 15 , 23 Two Bevacizumab studies were grouped together (Bevacizumab). 34 , 36 Nimotuzumab and Rindopepimut were combined (anti-EGFR); this is shown in Supplementary Figure 6B .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adjuvant therapies, such as chemotherapy and radiation, have a significant impact on patient survival, progression-free survival, and overall survival [38][39][40][41], and should be included in the standard of care for GBM patients alongside surgical treatment modalities. With a focus on the SVZ and high-dose proton beam treatment, Matsuda et al…”
Section: Discussionmentioning
confidence: 99%
“…Apart from surgical treatment strategies, adjuvant therapies including chemotherapy and radiotherapy should be considered in the standard of care for GBM patients as they also influence patient survival, PFS, and OS [ 5 , 49 51 ]. Matsuda et al [ 25 ] reported a median OS of 36.9 months for patients who underwent GTR of newly diagnosed GBM, with a particular focus on the influence of the subventricular zone (SVZ), combined with high-dose proton beam therapy, compared with a median OS of 26.2 months for patients treated with conventional radiotherapy.…”
Section: Discussionmentioning
confidence: 99%